Circle-Uniqueness of Pythagorean Orthogonality in Normed Linear Spaces - Senlin Wu; Xinjian Dong; Dan Wang (Journal of Function Spaces)
We introduce the circle-uniqueness of Pythagorean orthogonality in normed linear spaces and show that Pythagorean orthogonality is circle-unique if and only if the underlying space is strictly convex. Further related results providing more detailed relations between circle-uniqueness of Pythagorean orthogonality and the shape of the unit sphere are also presented.